Penerapan Aplikasi Markerless Augment Reality untuk Pemodelan Mesin Injection - Alvino Octaviano; Sofa Sofiana (Teknik Informatika Universitas Pamulang, 2019)
The limited number of teaching aids is the general shortage of private schools due to the limited cost of procuring props for the PGM-FI sistem. The less interesting learning model is also a factor in the low value of students in certain subjects. Augmented Reality is a technology that develops in the world, combining two-dimensional or three-dimensional virtual objects into a real three-dimensional environment and then projecting these virtual objects in real time. in previous studies have introduced Augmented Reality Applications that still use markers. But the application still has limitations. The need for paper printing and sticking to the object to be studied. Through markerless technology other than without the need for paper printing and pasting. This application can further adjust the appearance of injection machines